Aerobic swimming in intensive finfish aquaculture: applications for production, mitigation and selection. (29th June 2020) - McKenzie, David J.; Palstra, Arjan P.; Planas, Josep; MacKenzie, Simon; Bégout, Marie‐Laure; Thorarensen, Helgi; Vandeputte, Marc; Mes, Daan; Rey, Sonia; De Boeck, Gudrun; Domenici, Paolo; Skov, Peter V.
Abstract: We review knowledge on applications of sustained aerobic swimming as a tool to promote productivity and welfare of farmed fish species. There has been extensive interest in whether providing active species with a current to swim against can promote growth. The results are not conclusive but the studies have varied in species, life stage, swimming speed applied, feeding regime, stocking density and other factors. Therefore, much remains to be understood about mechanisms underlying findings of 'swimming‐enhanced growth', in particular to demonstrate that swimming can improve feed conversion ratio and dietary protein retention under true aquaculture conditions. There has also been research into whether swimming can alleviate chronic stress, once again on a range of species and life stages. The evidence is mixed but swimming does improve recovery from acute stresses such as handling or confinement. Research into issues such as whether swimming can improve immune function and promote cognitive function is still at an early stage and should be encouraged. There is promising evidence that swimming can inhibit precocious sexual maturation in some species, so studies should be broadened to other species where precocious maturation is a problem. Swimming performance is a heritable trait and may prove a useful selection tool, especially if it is related to overall robustness. More research is required to better understand the advantages that swimming may provide to the fish farmer, in terms of production, mitigation and selection.